LEADERSHIP AND COLLABORATION IN MICRO AND SMALL ENTERPRISES: A BIBLIOGRAPHICAL ANALYSIS OF ORGANIZATIONAL BEHAVIOR AND ITS INFLUENCES - Aparecida Sanches, Caroline; Camilli de Souza, Vitoria; Vancim Frachone Massa, Flávia (Revista Gênero e Interdisciplinaridade, 2025)
This article aims to analyze how leadership and collaboration influence organizational behavior in micro and small enterprises, considering their implications for business performance and sustainability. The research was developed using a qualitative approach, based on bibliographic and documentary analysis of relevant authors in the field of administration and organizational behavior. The results indicate that transformational leadership, associated with collaborative practice, is a determining factor in strengthening organizational culture, increasing motivation, and team engagement. It was found that ethical and emotionally intelligent leaders are able to promote environments of trust, efficient communication, and continuous innovation, fundamental elements for the competitiveness of small businesses. It was also found that collaboration strengthens the feeling of belonging and reduces turnover rates, contributing to collective performance. Thus, it is concluded that the synergy between leadership and collaboration is essential for building more resilient, innovative, and humanized organizations.